God, Can I Tell You Something? The Effect of Religious Coping on the Relationship between Anxiety Over Emotional Expression, Anxiety, and Depressive Symptoms - Bryan, Jennifer L. (Psycholog Relig Spiritual, 2015)
The current study investigated whether religious coping would moderate the association between ambivalence over emotional expression (AEE) and depressive symptoms and anxiety symptoms such that the positive relationship between AEE and depressive symptoms and anxiety symptoms would be weaker among those higher in religious coping. Three-hundred and fifty-two undergraduates (M age=23.51 years, SD=6.80; 84.4% female) completed study materials. Contrary to expectations, results revealed a significant interaction between religious coping and AEE such that religious coping exacerbated the relationship between higher AEE and distress symptoms. The implications of this study suggest that religious coping may not be an ideal coping mechanism for individuals with high levels of AEE. These results indicate the need to further examine the role of AEE in religious coping, and have potential implications for clinicians, healthcare professionals, and religious mentors who may promote the use of religious coping in treatment.